What parents and performers can do to support/supplement or replace the academy - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
The role played by families in the development of talent is well established in the literature. However, there is considerably less guidance available to parents and coaches about how good parenting style is operationalised within the development process; essentially, what is the balance between `pushy parenting` and under-involvement? This chapter provides guidance as to how the coach-athlete-family relationship can be managed and looks at effective parenting style in youth sport as well as exploring how siblings can be used to promote positive challenge along the pathway. It is also important that there is a coherence and shared understanding (or even agreed disharmony) between parents, the National Governing Body and coaches to ensure that these relationships facilitate rather than derail the development process. Suggestions about how to ensure this coherence are offered, supported by case studies from the perspective of key stakeholders in this process.